1986
DOI: 10.1037/0021-843x.95.4.378
|View full text |Cite
|
Sign up to set email alerts
|

Age at first onset for nonbipolar depression.

Abstract: The purpose of this study was to describe the onset age distribution for first episodes of unipolar depression for men and women. From a total of 6,742 participants ranging in age from 18 to 88 years, 2,046 were selected for a diagnostic interview on the basis of elevated scores on a self-report depression inventory and were diagnosed as per the Schedule for Affective Disorders and Schizophrenia and Research Diagnostic Criteria procedures. Of those interviewed, 1,012 were diagnosed as having suffered from a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
52
2
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 31 publications
7
52
2
3
Order By: Relevance
“…Epidemiological studies have reported prevalence rates of depression in adolescents ranging between .4% and 8.3% (e.g., Fleming & Offord, 1990;Lewinsohn, Hops, Roberts, Seeley, & Andrews, 1993). Furthermore, the lifetime prevalence of depression in adolescents varies between 15% and 20%, which is comparable with the lifetime rate in adults, suggesting that depression frequently has its onset in adolescence (e.g., Lewinsohn, Duncan, Stanton, & Hautziner, 1986).…”
Section: Introductionmentioning
confidence: 89%
“…Epidemiological studies have reported prevalence rates of depression in adolescents ranging between .4% and 8.3% (e.g., Fleming & Offord, 1990;Lewinsohn, Hops, Roberts, Seeley, & Andrews, 1993). Furthermore, the lifetime prevalence of depression in adolescents varies between 15% and 20%, which is comparable with the lifetime rate in adults, suggesting that depression frequently has its onset in adolescence (e.g., Lewinsohn, Duncan, Stanton, & Hautziner, 1986).…”
Section: Introductionmentioning
confidence: 89%
“…Second, a focus on college students is consistent with the results of epidemiological surveys of suicide and depression. A series of recent studies has pointed to the periods of adolescence and young adulthood as important times for the development of depression and related features such as suicide (Burke, Burke, Regier, & Rae, 1990;Lewinsohn, Duncan, Stanton, & Hautzinger, 1986;Sorenson, Rutter, & Aneshensel, 1991). First-year college students generally fall into one of the age groups for whom suicide rates have been increasing at an alarming rate (Berman & Jobes, 1991;Llopis, Beneyto, & Asencio, 1988).…”
Section: Studymentioning
confidence: 99%
“…The importance of early detection of mental disorders in preadolescence and adolescence is widely acknowledged, because these years are critical for the onset and development of later disturbances [8,10,32,34]. Therefore, accurate estimates of the prevalence of psychopathology for these age groups are essential for setting up adequate services, with the aim of diminishing the consequences of mental disorders on later development and functioning in adulthood.…”
Section: Introductionmentioning
confidence: 99%